Alternatives in Assessing Mental Healthcare Disparities Using the Behavioral Risk Factor Surveillance System - Jin Liu; Ning Jiang; Amy Z. Fan; Rebecca Weissman (Mary Ann Liebert, 2018)
Purpose: Identification of mental healthcare disparities through scales or questionnaires is an initial step to improve mental healthcare equity. This study was designed to investigate the performance of a single-item question relative to two psychiatric scales with multiple items in assessing mental healthcare disparities among U.S. adults using the Behavioral Risk Factor Surveillance System (BRFSS) data. Methods: The current depression (CD) and serious psychological distress (SPD) were analyzed in 2010 and 2012 with the BRFSS using two multiple-item scales in selected states. Receipt of mental health diagnosis and mental health treatment was ascertained respectively. In both years, a single item of the number of mentally unhealthy days from Centers for Disease Control Health-Related Quality of Life-4 (CDC-HRQOL-4) core questions was used to ascertain frequent mental distress (FMD) in all states. Logistic regression was used to identify mental healthcare disparities among subpopulations. The t-test was used to analyze missing data patterns. Results: Among adults who experienced FMD or CD in 2010, men, persons 65 years of age or older, non-Hispanic Blacks, persons who were currently or never married, and persons who were employed had a lower likelihood of receiving diagnosis of depression. Among adults who experienced FMD or SPD in 2012, men, persons 65 years of age or older, Hispanics and Blacks, persons who were currently employed or homemakers/students, and persons without healthcare coverage had a lower likelihood to receive mental health treatment. The missing rates of FMD were 1.8% (2010) and 1.4% (2012), while the missing rates of Patient Health Questionnaire 8 (PHQ-8) and Kessler 6 (K6) were 12.8% (2010) and 17.4% (2012). The samples with missing data were different from those without. Conclusions: The single-item question is a valuable alternative in a large population surveillance to identify vulnerable subpopulations for lower mental health diagnosis and treatment.